A case of choroidal metastasis from renal cell carcinoma significantly reduced by radiotherapy - Koichiro Kanazawa; Shinnosuke Oishi; Akihiko Sakamoto; Kuniaki Tanabe; Kazutaka Sugiyama; Akihiko Matsumoto; Akari Arakawa; Hiromi Matsunaga; Takafumi Harada; Haruki Kume (IJU Case Reports)
Introduction Choroidal metastasis from renal cell carcinoma is relatively rare and unresponsive to systemic treatment. Case presentation A man in his eighties with left renal cell carcinoma and pulmonary metastasis developed visual impairment in the left eye during primary treatment with ipilimumab and nivolumab followed by secondary treatment with cabozantinib. Consultation with an ophthalmologist revealed choroidal metastasis, which was subsequently treated with local radiotherapy (3 Gy × 10 Fr), resulting in a significant reduction in the metastatic lesions. Conclusion If visual impairment arises while treating renal cell carcinoma, it is essential to consider the possibility of intraocular metastasis. In terms of treatment, local therapies such as radiotherapy should be taken into consideration.